Male Age Influences Re-mating Incidence and Sperm Use in Females of the Dengue Vector Aedes aegypti - Agudelo, Juliana; Alfonso-Parra, Catalina; Avila, Frank W. (Frontiers in Physiology, 2021)
Diseases transmitted by female Aedes aegypti mosquitoes are public health issues in countries in the tropics and sub-tropics. As in other insects, Ae. aegypti females undergo behavioral and physiological changes upon mating that principally act to facilitate the production of progeny. The primary effectors of Ae. aegypti female post-mating responses are male-derived seminal proteins that are transferred to females during mating. Increased male age reduces ejaculate function in numerous taxa and alters seminal protein composition in Drosophila melanogaster, but the impacts of male age on female Ae. aegypti post-mating responses are unknown. Here, we used “old” (21-22 day-old) and “young” (4-5 day-old) Ae. aegypti males to assess the influence of male age on oviposition, fertility, and re-mating incidence in their mates. We also examined how age influenced paternity share in females initially mated to young or old males that subsequently re-mated with a transgenic male that transferred RFP-labeled sperm and whose progeny inherited a larval-expressed GFP marker. We found that increased male age had no effect on female fecundity or fertility but significantly impacted their ability to prevent re-mating in their mates—more than half (54.5%) of the females mated to an old male re-mated, compared to 24% of females initially mated to a young male. Polyandrous Ae. aegypti females displayed first male precedence regardless of the age of their initial mate. However, young males were better able to compete with rival male sperm, siring significantly more progeny (77%) compared to old males (64%). Young males had significantly more sperm in their seminal vesicles than old males at the time of mating, although males of both age groups transferred similar numbers of sperm to their mates. Our results suggest that male senescence differentially impacts the induction of some post-mating changes in Ae. aegypti females. As the effect of age may be further exacerbated in the field, age-related declines in male ability to induce sexual refractoriness has implications for Ae. aegypti population control programs that release adults into the environment.